Cyto-morphological abnormalities and cell membrane integrity of frozen-thawed spermatozoa of Frieswal bulls and their relationship with fertility - MANDAL, D K; TYAGI, S; KUMAR, M; MATHUR, A K (The Indian Journal of Animal Reproduction, 2007)
Frozen thawed semen of 5 adult Frieswal bulls were evaluated for motility (%), abnormalsperm cytomorphology and subjected to hypo-osmotic swelling (HOS) test to assess membrane integrityof the spermatozoa. Fertility rate of these bulls was assessed on a field based progeny testing programme.The over all post thaw motility and total abnormal spermatozoa in the thawed semen was 42.56±1.29and 14.26±0.04 %, respectively. The mean percentage ofabnormal ities in the head, mid piece and tailregion of the spermatozoa was 6.19±0.67, 4.37±0.35 and 3.70±0.35, respectively. The over all responseof spermatozoa in HOS solution was 33.67±1.25 % with a range of 30.50± 1.00 to 35.88±3.14 %among the bulls, and did not differ (P
Keywords: Sperm abnormality; Hypo-osmotic test; Frieswal bull; Fertility